2014
DOI: 10.4111/kju.2014.55.2.106
|View full text |Cite
|
Sign up to set email alerts
|

Sedoanalgesia With Midazolam and Fentanyl Citrate Controls Probe Pain During Prostate Biopsy by Transrectal Ultrasound

Abstract: PurposeTo assess the pain intensity of patients administered midazolam and fentanyl citrate before undergoing transrectal ultrasound-guided prostate biopsy.Materials and MethodsThis was a study in patients with different indications for prostate biopsy in whom 5 mg of midazolam and 50 µg of fentanyl citrate was administered intravenously 3 minutes before the procedure. After biopsy, pain was assessed by use of a visual analogue scale (VAS) in three stages: VAS 1, during probe introduction; VAS 2, during needle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
1
7
1
Order By: Relevance
“…According to our study, the mean pain scores during the rectal probe insertion were 4.46±0.505, 2.36±0.48, and 4.72±0.6, in groups 1, 2, and 3, respectively. The main difference between our work and the study of Tsuji et al is in the anesthesia technique (14). Their pain score was lower than ours, but their technique needs an anesthetist and longer hospital stay, besides, complications may occur depending on sedoanalgesia.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…According to our study, the mean pain scores during the rectal probe insertion were 4.46±0.505, 2.36±0.48, and 4.72±0.6, in groups 1, 2, and 3, respectively. The main difference between our work and the study of Tsuji et al is in the anesthesia technique (14). Their pain score was lower than ours, but their technique needs an anesthetist and longer hospital stay, besides, complications may occur depending on sedoanalgesia.…”
Section: Discussioncontrasting
confidence: 74%
“…In addition to these, one of the issues is discomfort and pain during probe insertion. According to Tsuji et al, the mean pain score was 2.73±2.55 during probe insertion under sedoanalgesia with midazolam and fentanyl citrate (14). Griwan et al showed that the mean pain score during the placement of the rectal probe was 4.85±1.09 under diclofenac pain control (15).…”
Section: Discussionmentioning
confidence: 99%
“…Of the patients studied, 72 (80%) reported that probe entry was disturbing and 18 (20%) reported it as painful. The pain level upon probe introduction was reported as 1.95 cm by Tsuji, et al and 1.56 cm by Tüfek, et al [14,17] In both studies, probe entry was found disturbing. Comparison of the present study with other studies may prove difficult because an evaluation of the use of VAS was not completed; however, the findings appear to be similar to other studies.…”
Section: Discussionmentioning
confidence: 87%
“…The pain was classified as follows: absence of pain, score of 0; mild pain, score of 0.1-3; moderate pain, score of 3.1-7; and severe pain, score of 7.1-10. [14] All biopsies were performed as outpatient procedures. The VAS score values of the patients in the first two groups were compared with those in Group III.…”
Section: Methodsmentioning
confidence: 99%
“…However, the number of biopsy specimens collected is not as important when using intravenous sedation and analgesia, as is performed when it is necessary to obtain a large number of fragments [29]. However, collection of a greater number of fragments could be a risk factor for complications after biopsy.…”
Section: Discussionmentioning
confidence: 99%